Scientific production of the journal Investigación y Educación en Enfermería during its 30 editing years - María de los Ángeles Rodríguez-Gázquez; Sara Janeth Chaparro-Hernández; Warley Mateo Rojas-Minota (Universidad de Antioquia, 2013)
Objective. This study sought to characterize the scientific production of the journal Investigación y Educación en Enfermería (IEE) during its 30 years of editing. Methodology. Documentary type longitudinal study, which analyzed all the articles published in IEE from 1983 to 2012; a total of 656. Each article was manually revised and an instrument was used containing the variables of author and article characteristics. Results. A total of 47% of the articles have a sole author and only one institution of affiliation. According to their type, those with the most contributions were original articles (42%) and theme reviews (25%). Regarding the characteristics of the first authors, nurses predominate (74%); with graduate formation (71%); with academic affiliation (88%); and country of origin being Colombia (70%). The principal themes dealt with are: nursing care (24%), nursing education and formation (14%), nursing practice (6%), and nursing history (5%). The most frequent populations objects of study are nurses (25%) and nursing students (8%). A total of 15% deal with vulnerable populations (elderly, children, pregnant women, the handicapped, and individuals from rural areas, among others). Additionally, the following tendencies were noted: authors have improved in their levels of formation, and regarding the increased number of original articles and balance per type of research paradigm. Conclusion. Author's characteristics and thematic preferences, along with populations object of the articles show that progress has been produced in divulging knowledge generated and of the experiences in their implementation in nursing practice, thus, contributing to the discipline's development.